Integrating biodiversity and ecosystem services into the economic analysis of agricultural systems - Regmi, A.; Rojas Lara, T.; Kleinwechter, U.; Conwell, A.; Gotor, Elisabetta (2016)
Based on existing literature, this paper outlines the relationships between biodiversity, ecosystem services and food security. It additionally reviews tools which can be used to integrate biodiversity and ecosystem services into analytic frameworks to allow a better understanding of the trade-offs between different agricultural systems and their ecosystem service provisioning, as well as the resulting impact on productivity and human well-being.